Claroscuros del proceso electoral 2023 - Rosero Escalante, Andrés (2023)
The Electoral process of February 2023 left results which reconfigured the Ecuador's political map. Based on the data, and with the perspective of economic and political critic, this paper analyzes the panorama was configured. This has allowed visualizing, from the data and since a historical and structural approach, the interests at stake in electoral situation, and the trends which consolidated, the possibilities and limits they have, especially representative democracy's crisis. These results point out to a hegemony crisis that, however, not guarantees the consolidation of a popular alternative what pick up the most population strategic interest.